Environmentally Friendly Synthesis of Ferric Chloride Coagulant from Scrap Iron for the Reduction of ion ferro and Total Dissolved Solids - Sumardiyono; Sunardi; Argoto Mahayana; Nur Hidayati; Soebiyanto; Mahardira Dewantoro; Afif Afghohani (Jurnal Serambi Engineering, 2026)
The decline in groundwater quality, particularly in terms of TDS and Fe²⁺ levels, is a major concern in clean water supply. This study aims to synthesize and evaluate the effectiveness of FeCl₃ coagulant synthesized from scrap iron waste from a lathe workshop in reducing Total Dissolved Solids (TDS) and Fe²⁺ levels in borehole water. FeCl₃ was synthesized by reacting scrap iron waste with a 32% HCl solution. Water samples were tested for TDS and Fe²⁺ levels before and after treatment using gravimetric and UV-Vis spectrophotometric methods. The FeCl₃ coagulant doses used were 0.1%, 0.2%, and 0.3%. The results showed that the 0.3% dose provided the highest effectiveness in reducing Fe²⁺ levels by 80.10%, while the reduction in TDS reached 36.05% at the same dose. All doses successfully reduced Fe²⁺ levels to below the threshold set by Ministry of Health Regulation No. 2 of 2023 (<0.2 mg/l). This study demonstrates that FeCl₃ coagulant derived from iron waste is effective and has the potential to serve as an economical and environmentally friendly alternative for water treatment.